2014
DOI: 10.20961/agsjpa.v16i1.18906
|View full text |Cite
|
Sign up to set email alerts
|

Pertumbuhan Tomat pada Frekuensi Pengairan yang Berbeda

Abstract: <p>Tomato (Lycopersicum esculentum Mill) is one of horticulture commodities with high economic value and still need seriously handling especially for increasing fruits quality and quantity. However the production of tomato has not fullfilleed the demand yet. Therefore it is necessary to develop production. On lowland, the issue not only high temperature but also availability of water is unpredictable.This study aimed to investigate the effect of irrigation frequency on the growth of Mutiara, Opal, and Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
4
0
4
Order By: Relevance
“…Salinity can improve the quality of tomatoes (Jumawati et al, 2014), caused by increased solute through the arrangement of osmotic potential. Salinity can also increase the antioxidant content in the fruit (Gautier et al, 2010).…”
Section: Total Vitamin C and Flavonoid Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Salinity can improve the quality of tomatoes (Jumawati et al, 2014), caused by increased solute through the arrangement of osmotic potential. Salinity can also increase the antioxidant content in the fruit (Gautier et al, 2010).…”
Section: Total Vitamin C and Flavonoid Contentmentioning
confidence: 99%
“…Tomatoes are plants derived from the family Solanaceae susceptible to water shortages during infancy (Lestari; Jumawati et al, 2014). Drought events cause lack of water in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rendahnya nilai pertambahan tinggi tanaman tomat mutan Sletr1-2 dalam kondisi cekaman kekeringan diakibatkan oleh pertumbuhan daun (Tabel 2), dan akar yang terhambat (Tabel 3), sehingga tomat mutan Sletr1-2 terganggu kemampuan berfotosintesisnya. Jumawati et al (2014) Jumlah daun tomat mutan NIL Sletr1-2 dan BC3F1Sletr1-2 lebih sedikit dibandingkan dengan tomat Intan pada kondisi cekaman kekeringan. Hal tersebut disebabkan oleh pertumbuhan akar kedua tomat mutan yang terhambat (Tabel 3) dan akibat kematian sel yang terjadi pada bagian daun tanaman yang disebabkan oleh akumulasi ROS (Reactive Oxygen Species) pada jaringan tanaman (Poóret al, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…Irrigation influences many plant attributes of tomato, such as the height of the plant, the number of leaves, the number of branches, etc. Practicing irrigation less on tomatoes often reduces the growth and physiological components but increases fruit quality (Jumawati et al, 2014). Xiukang and Yingying (2016) reported that increasing irrigation level influenced the increase in tomato fruit yield, fertilizer rate, and decreased water use efficiency.…”
Section: Introductionmentioning
confidence: 99%